Upper Extremity Catheter Angiography: Indications, Techniques, Anatomy, and Classic Cases - Shin, David S.; Magill, David B.; Johnson, Guy E.; Ingraham, Christopher R.; Kogut, Matthew J.; Monroe, Eric J. (Journal of Clinical Interventional Radiology ISVIR, 2018)
Catheter arteriography of the upper extremity has become an infrequent procedure in modern practice given the advancements in computed tomography/magnetic resonance angiography (CT/MRA). However, catheter angiography continues to have major diagnostic and interventional roles in certain pathophysiologic conditions. This article discusses the indications and techniques of upper extremity catheter angiography, and presents classic cases to demonstrate key anatomic, diagnostic, and interventional considerations.
Keywords: upper extremity; artery; angiography